2006
DOI: 10.1007/s00441-006-0178-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces production of nitric oxide and reactive oxygen species in glomus cells of rat carotid body

Abstract: The carotid body is an arterial chemoreceptor organ that senses arterial pO(2) and pH. Previous studies have indicated that both reactive oxygen species (ROS) and nitric oxide (NO) are important potential mediators that may be involved in the response of the carotid body to hypoxia. However, whether their production by the chemosensitive elements of the carotid body is indeed oxygen-dependent is currently unclear. Thus, we have investigated their production under normoxic (20% O(2)) and hypoxic (1% O(2)) condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 54 publications
0
36
0
1
Order By: Relevance
“…23 These reactive oxygen and nitrogen radicals are produced after oxygen supply interruption and/or restoration. 3,24 The major intracellular sources of O 2 À are the electron transport chain in the mitochondria, the nicotinamide adenine dinucleotide dihydrophosphate (NADPH) oxidase, cytochrome P450 reductase system in the cellular plasma membrane, 1,2 and the xanthine oxidase 25 and NO synthase (NOS) 26,27 enzyme systems (Figure 1). Xanthine oxidase synthesizes O 2 À and is one of the major O 2 À -producing enzymes.…”
Section: Molecular Processes Involved In the Generation Of Free Radicmentioning
confidence: 99%
See 1 more Smart Citation
“…23 These reactive oxygen and nitrogen radicals are produced after oxygen supply interruption and/or restoration. 3,24 The major intracellular sources of O 2 À are the electron transport chain in the mitochondria, the nicotinamide adenine dinucleotide dihydrophosphate (NADPH) oxidase, cytochrome P450 reductase system in the cellular plasma membrane, 1,2 and the xanthine oxidase 25 and NO synthase (NOS) 26,27 enzyme systems (Figure 1). Xanthine oxidase synthesizes O 2 À and is one of the major O 2 À -producing enzymes.…”
Section: Molecular Processes Involved In the Generation Of Free Radicmentioning
confidence: 99%
“…28 Nitric oxide, also known as endothelium-derived relaxing factor, is a key biological messenger that is synthesized endogenously during conversion of arginine to citrulline in a process that required molecular oxygen and NADPH with tetrahydrobiopterin (H 4 B) acting as a cofactor. Bioregulatory NO is generated by 3 isoforms of NOS enzymes, 26,27 namely, neuronal NOS (nNOS), endothelial NOS (eNOS), and inducible NOS (iNOS). Although the former 2 are calcium dependent for their regulation, iNOS is insensitive to endogenous calcium, likely due to its tight noncovalent interaction with calmodulin (CaM) and Ca 2þ .…”
Section: Molecular Processes Involved In the Generation Of Free Radicmentioning
confidence: 99%
“…Nitric oxide can contribute to mitochondrial superoxide formation (Yamamoto et al, 2006), and bind to and inhibit cytochrome oxidase, thereby causing the reduction of upstream electron carriers and favoring additional superoxide formation (Cooper and Davies, 2000).…”
Section: Negative Effects Of Hypoxiamentioning
confidence: 99%
“…Moreover, pure oxygen is linked to the oxidative injury of mitochondrial enzymes such as cytochrome c oxidase (complex IV) (Walker and Benzer, 2004), aconitase and adenine nucleotide translocase (Das et al, 2001;Yan and Sohal, 1998), and induces brain damage (Kloek et al, 1978;Philpott et al, 1974), apotosis (Oh et al, 2008) and lung damage (Bin-Jaliah et al, 2009;Pace et al, 2009). Similarly, extreme hypoxia, and hypoxia followed by reoxygenation (reperfusion), can promote free radical production in vivo, as well as many types of oxidative injury Dirmeier et al, 2002;Duranteau et al, 1998;Yamamoto et al, 2006). Reported oxidative stress in both 100% oxygen atmospheres and extreme hypoxia suggests that the relationship between atmospheric oxygen level and oxidative damage is non-linear and perhaps parabolic in shape.…”
Section: Introductionmentioning
confidence: 99%
“…During hypoxia, elevation of intracellular calcium in the chemosensitive glomus cell is essential for the chemotransduction. In fact, a recent study has demonstrated morphological evidence supporting an increase in NO production in the glomus cell during acute hypoxia [38]. Thus, the NO released by the glomus cell could contribute to the hypoxiainduced NO elevation in the carotid body.…”
Section: Discussionmentioning
confidence: 94%